The effect of Industry Homogeneity on the Magnitude of Post- earnings Announcement Drift: Evidence from Korea - Heejeong Shin,; Su-In Kim,; Sorah Park,; Hyejeong Shin, (Asian Academy of Management Journal of Accounting and Finance, 2019)
We examine the relationship between industry homogeneity and the magnitude of post-earnings announcement drift (hereafter, PEAD). Given that firms with more homogeneous operating cost structure are conducive to spillover of knowledge among investors, we expect that firms in highly homogenous industries have relatively low magnitude of PEAD. Using firms listed on the Korean Stock Exchange, we find that the magnitude of PEAD is negatively related to industry homogeneity, indicating that investors are more efficient for firms in a highly homogenous industry in which information is likely to be referred to peer firms. In addition, we find that the effect of industry homogeneity on the magnitude of PEAD is robust even after controlling to the effect of industry concentration. Our study contributes to the literature on exploring determinants of PEAD by linking information transfer effect in a homogenous industry to investors’ informational efficiency in capital markets.